Cultural Resistance and Sharia-Based Ecology in the Fishing Community in Aceh - Zubir Zubir; Abdul Manaf; Noviandy Noviandy; Abdul Mugni (Al-Albab, 2022)
This article examines the cultural resistance and sharia-based environmental management in the fishing community in Aceh Timur Raya, Indonesia. Aceh is a fascinating Indonesian region as the country’s implementer of Islamic law.  To date, Aceh’s environment has yet to become an issue that needs to be immediately addressed. This study is classified as field-library research with a qualitative analysis. The data were collected using interviews, documentation, and observations of fishermen’s environment in Aceh Timur Raya. These data were analyzed using a sociological approach, social theories, power-knowledge relations, and habitus. This study found several important reasons why there could be damage to Aceh Timur Raya’s ecosystems. This article has produced several vital findings; First, the absence of the role of religion in maintaining and building an ecological culture in the fishing community. Second, the attitude of indifference among the fishing community towards the environment. Third, the politicization of environmental care. These three pieces of evidence state that cultural resistance and sharia-based environmental management in Aceh threaten the community's survival, especially fishermen who rely heavily on nature. Islamic law has not been able to base its teachings on the environment that must be preserved and developed.